Do we need to listen to all stakeholders? Communicating in a coordination game with private information - Antonio Cabrales; Michalis Drouvelis; Zeynep Gurguc; Indrajit Ray (Cardiff University, Cardiff Business School, 2018)
We consider an experiment with a version of the Battle of the Sexes game with two-sided private information, preceded by a round of either one-way or two-way cheap talk. We compare different treatments to study truthful revelation of information and subsequent payoffs from the game. We find that the players are overall truthful about their types in the cheap-talk phase in both one-way and two-way talk. Furthermore, the unique symmetric cheap-talk equilibrium in the two-way cheap talk game is played when the players fully reveal their information; however, they achieve higher payoffs in the game when the talk is one-way as the truthful reports facilitate desired coordination.
Keywords: C72; C92; D83; 330; Battle of the Sexes; Private Information; Cheaptalk; Coordination